Deux inscriptions funéraires byzantines du Sinaï nord-ouest (Collection Starcky) - Puech, Émile (Liber Annuus, 2024)
Abstract Two short Greek funerary inscriptions from the Byzantine period, bought by Jean Starcky during his stay at the École biblique et archéologique française as editor of the Dead Sea Scrolls, and left among his belongings in the cellar of the school, are still unedited. Starcky had the intention to join them with the other objects of the small Musée Bible et Terre Sainte at the Institut Catholique of Paris. The inscriptions are said to come from the area around Lake Bardawil.